Lack of facilities rather than sociocultural factors as the primary barrier to physical activity among female Saudi university students - Samara A; Nistrup A; AL-Rammah TY; Aro AR (Dove Medical Press, 2015)
Anastasia Samara,1 Anne Nistrup,1 Tamader Y AL-Rammah,2 Arja R Aro11Unit for Health Promotion and Research, University of Southern Denmark, Esbjerg, Denmark; 2Faculty of Rehabilitation and Health Sciences, Princess Nora Bint Abdul Rahman University, Riyadh, Kingdom of Saudi ArabiaPurpose: The Kingdom of Saudi Arabia is experiencing a dramatic increase in physical inactivity, with women having higher levels of inactivity than men among all age groups. It is assumed that factors such as dress codes, restrictions on going outdoors, and conservative norms are the main reasons for women’s low physical activity. Our aim was to explore the different parameters related to physical activity, including self-efficacy, as well as the perceived barriers to and benefits of physical activity in young Saudi females.Patients and methods: Ninety-four first-year female Saudi university students in Riyadh, Kingdom of Saudi Arabia, participated in the present study in 2014. The students were from eight bachelor’s programs in health and well-being, and each completed a questionnaire with questions divided into five parts as follows: 1) socioeconomic status, 2) physical activity, 3) self-efficacy 4) social factors, and 5) barriers and facilitators related to physical activity.Results: The students exercised at home and alone, and there was low self-efficacy for physical activity (mean score =42±14). Among social factors, attending university was the only factor that hindered physical activity (32%). Physical activity was positively perceived overall (mean score =131±10). Students showed awareness of the benefits of physical activity for health and well-being. The most important barrier was the lack of designated areas available for physical activity. Students disagreed that family or the Islamic community were barriers to physical activity.Conclusion: The lack of facilities and lack of encouragement from the university, but not a lack of knowledge (a high level of knowledge is to be expected given their health and well-being studies backgrounds) and/or restrictions from families and society, seem to hinder female students’ physical activity, at least young Saudi students.Keywords: physical activity, Kingdom of Saudi Arabia, females, barriers and facilitators, self-efficacy